2006
DOI: 10.1196/annals.1378.077
|View full text |Cite
|
Sign up to set email alerts
|

Altered Gene Expression Pattern in Peripheral Blood Leukocytes from Patients with Arterial Hypertension

Abstract: The role of various inflammatory mechanisms and oxidative stress in the development of atherosclerosis and arterial hypertension (AH) has been increasingly acknowledged during recent years. Hypertension per se or factors that cause hypertension along with other complications lead to infiltration of activated leukocytes in the vascular wall, where these cells contribute to the development of vascular injury by releasing cytokines, oxygen radicals, and other toxic mediators. However, molecular mechanisms underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 30 publications
(25 reference statements)
1
9
0
3
Order By: Relevance
“…Therefore, our results show that the analysis of atherogenic‐related PBMC gene expression, specifically IL4 expression, could be an interesting diagnostic tool with clinical application for diagnosis of asymptomatic peripheral atherosclerosis disease. These results are in line with previous investigations showing the utility of blood cell in vivo transcriptome in the search of CVD biomarkers , in particular of atherosclerotic‐related disease biomarkers . Interestingly, the PBMC gene expression profile that we have identified in subclinical femoral atherosclerosis is different from that previously reported in coronary or carotid atherosclerosis .…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, our results show that the analysis of atherogenic‐related PBMC gene expression, specifically IL4 expression, could be an interesting diagnostic tool with clinical application for diagnosis of asymptomatic peripheral atherosclerosis disease. These results are in line with previous investigations showing the utility of blood cell in vivo transcriptome in the search of CVD biomarkers , in particular of atherosclerotic‐related disease biomarkers . Interestingly, the PBMC gene expression profile that we have identified in subclinical femoral atherosclerosis is different from that previously reported in coronary or carotid atherosclerosis .…”
Section: Discussionsupporting
confidence: 89%
“…Third, it remains to be determined whether the TAA signature can be applied to detect abdominal aortic aneurysms (AAA), especially since it has been shown that patients with descending TAA were likely to have kindred with AAA [33]. Preliminary analysis showed no significant overlapping between the TAA signature genes identified in this study and those reported for other vascular diseases such as atherosclerosis [10], coronary artery disease[11], [12] and arterial hypertension [13], suggesting that this signature is specific to TAA rather than a general signature for vascular disease or inflammation. Finally, although we believe the TAA classifier genes identified in this study define potential diagnostic markers for TAA, we want to emphasize that further study needs to be done before clinical application, including independent validation (retrospective and prospective) with larger numbers of subjects and determining the positive prediction value (PPV) and negative prediction value (NPV) in the context of a clinical diagnostic test.…”
Section: Discussionmentioning
confidence: 77%
“…These signatures genes have been also shown to be useful in identifying pathways relevant to disease[8] and in predicting response to therapy [9]. Recent studies have also provided evidence that blood cell gene expression profiling might have utility in the detection of complex cardiovascular diseases such as atherosclerosis [10], coronary artery disease [11], [12], and arterial hypertension [13].…”
Section: Introductionmentioning
confidence: 99%
“…Circulating peripheral blood cells have been used to examine differentially regulated genes in several cardiovascular disorders. For example, gene expression profiling studies of blood cells have identified differentially regulated genes and pathways in hypertension [9], coronary artery disease [10,11] and ischemic stroke [1,10,12-16]. However, genes differentially expressed in PBMC in the setting of PAD have yet to be identified.…”
Section: Introductionmentioning
confidence: 99%